2016
DOI: 10.1080/13669877.2016.1223163
|View full text |Cite
|
Sign up to set email alerts
|

Cattle farmers’ perceptions of risk and risk management strategies: evidence from Northern Ethiopia

Abstract: This study analyzes cattle farmers' perceptions of risk and risk management strategies in Tigray, Northern Ethiopia. We use survey data from a sample of 356 farmers based on multistage random sampling. Factor analysis is employed to classify scores of risk and management strategies, and multiple regression is then used to investigate the relationship of scores and farmers' characteristics. The results demonstrate that shortage of family labor, high price of fodder and limited farm income were perceived as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 53 publications
9
50
3
Order By: Relevance
“…Bardhan et al (2006) found that as herd size increases, the more risk averse the farmers, mainly attributed to farmers paying more attention to their farming. This was contrary to Bishu et al (2016) who found that in Ethiopia, as herd size increased, farmers became less risk-averse. This was also supported by Van Winsen et al (2016) and Xiao et al (2001) who indicated that the larger the farm size, the less risk averse the farmer.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…Bardhan et al (2006) found that as herd size increases, the more risk averse the farmers, mainly attributed to farmers paying more attention to their farming. This was contrary to Bishu et al (2016) who found that in Ethiopia, as herd size increased, farmers became less risk-averse. This was also supported by Van Winsen et al (2016) and Xiao et al (2001) who indicated that the larger the farm size, the less risk averse the farmer.…”
Section: Resultscontrasting
confidence: 90%
“…Hence, they are less likely to experiment and expose to risk unless their livelihoods be compromised. This was contrary to Bishu et al (2016) and Meuwissen, Huirne, and Hardaker, (2001) who found that the higher the farm income, the less risk averse the farmers. However, Mischra and Goodwin, (2006) indicated that it is actually the amount of off/non-farm income that would make farmers less risk-averse.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…These contextualized questions follow other studies (e.g. Bishu, O'Reilly, Lahiff, & Steiner, 2016;Flaten et al, 2005;Meuwissen et al, 2001;van Winsen et al, 2014) ensuring comparability of results. This method is simple, fast to complete and allows for domain specific contextualization, i.e.…”
Section: Business Statements (Bs)mentioning
confidence: 99%
“…Felleke and Geda (2001) also stated that 73 percent of the feed is provided from natural grazing, 14 percent from crop residues, and the remaining 13 percent from other feed sources. A recent study by Bishu (2014) in Tigrai indicated that there is a livestock drinking water shortage (34 percent) and feed shortages (7 percent). There is also a livestock management labor shortage (Tegegne 2012).…”
Section: Description Of the Study Area And Datasetmentioning
confidence: 99%